Pengaruh Kompensasi Finansial Dan Stres Kerja Terhadap Kinerja Karyawan Melalui Motivasi Kerja Sebagai Varibel Moderating Pada Pekerja CV MT Tani - Wayan Yogi Krismonica; Darmawan; Fauzan Ramadhan (Jurnal Manajemen DIVERSIFIKASI, 2025)
The purpose of this study was to determine the effect of financial compensation and workstress on employee performance moderated by employee work motivation. This study appliesquantitative research that measures the variables of financial compensation, work stress,employee performance, and work motivation using a questionnaire through a Likert scalescoring of 1-5. This study involved a population of 32 employees. The sampling techniqueused in this study was saturated sampling. Data collection using a questionnaire and dataanalysis using Moderate Regression Analysis (MRA). The results of the study indicate thatFinancial Compensation has an effect and is significant on employee performance. Theaspect that has the most effect on financial compensation on employee performance is thecompensation applied by the company and the weakest is the applicable regulations. Workstress has a negative and significant effect on employee performance. The aspect that has themost effect on work stress is physical demands and the weakest is task demands. Workmotivation can significantly strengthen the effect of financial compensation on employeeperformance at CV MT Tani. Work motivation can strengthen the effect of work stress onemployee performance. Work motivation reduces excessive work stress in employess